Formulation and Evaluation of Gel of Binahong Leaves Nanoparticle Extract (Anredera cordifolia (Ten.) Steenis) as an Antioxidant and Sunscreen - Fathiyah Ghina; Ro’ufi Absor; Deni Rahmat (Journal of Natural Product for Degenerative Diseases, 2025)
Binahong leaves are a herbal plant that is used to cure several diseases in Indonesia. Binahong leaves have flavonoids that can be potentially beneficial for antioxidants and sunscreen. The study aims to formulate an extract and a nanoparticle extract from binahong leaves into a gel and determine antioxidant and sunscreen activity. Binahong leaves were macerated using 70% ethanol and concentrated with a rotary evaporator. Then the extract was made into nanoparticles using the ionic gelation method. The nanoparticles were characterized for particle size, zeta potential, and morphological shape. The results showed that the nanoparticles were 192.7 nm in size, zeta potential of +25.3 mV, and spherical in shape. Antioxidant and sunscreen activity tests were analyzed using a UV-Vis spectrophotometer. Determination of antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenger activity method. The binahong leaves extract and nanoparticles had IC50 values of 68.78 ppm (moderate) and 152.18 ppm (weak). The antioxidant gel binahong leaves had IC50 of Formula II (174.85 ppm) and Formula III (221.14 ppm). The sunscreen activity was analyzed by determining the SPF value. Binahong leaves extract and nanoparticles had SPF values of 16.92 and 21.55 (ultra category). The sunscreen gel binahong leaves extract (formula II) and nanoparticles (formula III) had SPF values of 2.61 and 3.3 (minimal category). Gel preparations were evaluated, including organoleptic, homogeneity, spreadability, viscosity, and pH test. Binahong leaves extract and nanoparticles extract had antioxidant activity and SPF value that could be formulated into a gel preparation.